SPECIFIC CHARACTERISTICS OF INDUSTRIAL NETWORK EFFICIENCY ASSESSMENT IN THE REGIONS (Marketing Journal, 2025)
The article summarizes the views of scientists on the efficiency and economic efficiency of industry on territorial features and develops the authorʼs approach. With the help of economic and statistical methods, the criteria for the development of industry in the Khorezm region and its economic efficiency are studied. Based on the results obtained, proposals are formulated to improve the economic efficiency of industry in the region and their region.
Keywords: industry; efficiency; region; labor productivity; capital productivity; correlation; regression; statistical analysis